Community service: A case study in the faculty of business management, UiTM Pahang / Musramaini Mustapha, Nor Hidayatun Abdul Razak and Suhanom Mohd Zaki - Mustapha, Musramaini; Abdul Razak, Nor Hidayatun; Mohd Zaki, Suhanom (2012)
Most of the students tend to participate in community services because they enjoy being in the program or they are asked to participate even though without their concern on the effect of community services activity to their own personal feelings, values and experiences in achieving a better standard in what they do in life. The purpose of this paper is to explore the experience and knowledge about community service activity among the low grade students. Besides that, the researchers would like to identify the attitudes and perceptions of the low grade students on the community service learning module as part of the requirements in their academic program. The Community Service-Learning Attitudes and Perceptions Scale (CSLAPS) was used to analyze the data. The findings showed that those students tended to participate in community services because of their interest on that programme itself and for their career development. This information could be used by the academia to address students' tendency to get involved in community service activities as one of academic programmes to enhance their learning experience.